Movements and Its In-Process Control of Ground and Built Structures due to Tunnelling in Urban Areas. (29th January 2022) - Zhang, Dingli; Cao, Liqiang; Fei, Jianbo; Fang, Huangcheng; Yu, Lin; Hong, Xuefei
Abstract : Tunnelling-induced environmental responses including ground movements and deformation of the environmental structures are the two prominent issues needed to be carefully disposed in urban areas. This paper tries to develop a theoretical framework to evaluate and control the environmental deformation to avoid two disasters including ground collapse and structural failure. According to the mechanical responses of the ground due to tunnelling, the urban ground in China can be roughly divided into three types including composite multilayered ground, highly water-bearing ground, and mixed rock ground. The displacements of ground and environmental structures due to tunnelling in multilayered ground are emphatically discussed in view of its largest proportion distribution. The cumulative and mutational characteristics of the displacements are considered, which can be the main basis for distinguishing the occurrence of two types of disasters. Based on the development of the displacements, the three-stage evolution model of disaster is established. Combined with the existing displacement and degeneration of the ground and structures and the safety factor, the displacement control standards can be eventually determined. The theoretical framework of in-process control is established which is based on the prediction, measurement, and control standards of the displacements. In the framework, the prediction model can be modified in time, and the tunnelling parameters can be adjusted synchronously. The current research is successfully applied in the Qinghuayuan Tunnel Project.